Photodynamic Therapy of Novel Photosensitizer Ameliorates TNBS-Induced Ulcerative Colitis via Inhibition of AOC1 - Rong, Yumei; Hong, Ge; Zhu, Na; Liu, Yang; Jiang, Yong; Liu, Tianjun (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC), a chronic, nonspecific inflammatory bowel disease characterized by continuous and diffuse inflammatory changes in the colonic mucosa, requires novel treatment method. Photodynamic therapy (PDT), as a promising physico-chemical treatment method, were used to treat UC rats’ model with novel photosensitizer LD4 in this paper, the treatment effect and mechanism was investigated. LD4-PDT could improve the survival rate of 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced UC model rats, decrease expression of interleukin (IL)-6, IL-1, tumor necrosis factor (TNF)-α, malondialdehyde (MDA), myeloperoxidase (MPO) and increase the expression of glutathione (GSH) and superoxide oxidase (SOD), while protecting the integrity of the intestinal epithelium. LD4-PDT treatment could rebuild the intestinal microflora composition and reprogram the colonic protein profiles in TNBS-induced rats to almost the normal state. Proteomics analysis based upon TNBS-induced UC model rats revealed that Amine oxidase copper-containing 1 (AOC1) was a potential target of LD4-PDT. Novel photosensitizer agent LD4-PDT represents an efficient treatment method for UC, and AOC1 may be a promising target.